Angels & demons - Brown, Dan, 1964-; Poe, Richard; Recorded Books, Inc.; Findaway World, LLC.; Playaway Digital Audio (2006)
Harvard symbologist Robert Langdon is summoned to Switzerland when the dead body of a famous physicist turns up. Inspecting the deceased, Langdon is startled to see a highly unusual mark on his chest--the symbol of the ancient brotherhood of the "Illuminati." Soon, Langdon and his partner, scientist Vittoria Vetra, assemble evidence pointing to a reemergence of this mysterious cult. Is it possible that this secret society could still be obsessed with destroying Catholicism after all these centuries? When an unimaginably powerful new weapon is introduced into the mix, Langdon and Vetra are thrust into an amazing adventure in search of the fabled Illuminati lair.
Issued on Playaway, a dedicated audio media player, manufactured by Findaway World, LLC.
Narrated by Richard Poe.
Keywords: Physicists -- Crimes against -- Fiction; Religious educators -- Fiction; Popes -- Election -- Fiction; Signs and symbols -- Fiction; Secret societies -- Fiction; Anti-Catholicism -- Fiction; Illuminati -- Fiction; Vendetta -- Fiction; Playaway (Preloaded audio player); Vatican City -- Fiction; Audiobooks; Thrillers (Fiction).